Perspectives on Economic Development Public Policy, Culture, and Economic Development - Merlin Yonk, Ryan; Bobek, Vito (IntechOpen, 2020)
Among the most discussed and contested areas of policy are those that surround economic development. Among the wide universe that is public policy, those policies that claim to enhance economic development have long been viewed as particularly important, and discussions over what the best approaches are have been varied, heated, and often at the core of the success or failure of governments. This volume explores how different policy environments impact economic development in light of the interplay with other factors. From discussion of tax policy in the Russian Federation, to the interplay of economic development and culture in Namibia, to the complex interplay between tourism and extractive industries in the United States, this volume explores a range of policy realities.